Nilai Gizi dan Sifat Organoleptik Sosis Daging Sapi dengan Penambahan Pasta Buah Merah pada Level yang Berbeda - Surbakti, E.; Arief, I. I.; Suryati, T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Red fruit pasta are reported containing active components that are important to health, so the opportunities to be developed into a functional food ingredients. The purpose of this study is utilize pasta as natural dye in beef sausage and based on chemical quality and sensory. Given some active compounds are known to display as natural dye for food.  In this study, beef sausage was added by red fruit pasta in various concentrations: (0%, 7%, 9%, and 11%) were added on beef sausage. The observed variables were chemical qualities (water content, protein content, fat content, ash content and carbohydrate content) and sensory (colour, taste, texture, and aroma). The result showed that the addition of red fruit pasta on beef sausage significantly affected on water content and protein content. Organoleptic testing (hedonic and hedonic quality testing) showed that the panelists remarkably prefered all beef sausages with addition of red fruit pasta